2017
DOI: 10.1111/ene.13334
|View full text |Cite
|
Sign up to set email alerts
|

Migraine associated with altitude: results from a population‐based study in Nepal

Abstract: Background and purposeA 1988 pilot study in Peru suggested an association between migraine and chronic exposure to high altitude. This study provides epidemiological evidence corroborating this.MethodsIn a cross‐sectional nationwide population‐based study, a representative sample of Nepali‐speaking adults were recruited through stratified multistage cluster sampling. They were visited at home by trained interviewers using a culturally adapted questionnaire. The altitude of dwelling of each participant was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…There were no differences between low and intermediate altitudes, while above 2000 m there was a trend towards less prevalent migraine. In Nepal, an LTB-supported study (using the same methodology) found a very strong relationship between migraine prevalence (and indices of severity) and altitude up to 2000 m [30, 35], which is not reflected here. Explanation comes to mind: we only had approximations of altitude of each household, and the spread was rather narrow – certainly not as wide as in Nepal [35].…”
Section: Discussionmentioning
confidence: 68%
“…There were no differences between low and intermediate altitudes, while above 2000 m there was a trend towards less prevalent migraine. In Nepal, an LTB-supported study (using the same methodology) found a very strong relationship between migraine prevalence (and indices of severity) and altitude up to 2000 m [30, 35], which is not reflected here. Explanation comes to mind: we only had approximations of altitude of each household, and the spread was rather narrow – certainly not as wide as in Nepal [35].…”
Section: Discussionmentioning
confidence: 68%
“…A point worthy of emphasis here is that these indices of symptom severity are, clearly, key indicators of need for headache services. We have previously shown that all symptom indices increase with altitude of dwelling across the range < 500 m to 2499 m [36], and this was reflected here in the greater use of medication by high-altitude dwellers. Clearly, this relative excess of need among high-altitude dwellers presents a major challenge to equitable provision of headache services in Nepal.…”
Section: Discussionmentioning
confidence: 73%
“…This intervention would require greater knowledge of the modifiable factors that drive headache: several have been suggested with varying degrees of scientific support, such as obesity, smoking, indoor and outdoor air pollution, level of physical activity, altitude, blood pressure, and level of stress. 29 , 30 , 31 , 32 Of these factors, altitude and stress are not included as risks in GBD. For the other postulated risks, the evidence for an effect on headaches is, in our opinion, insufficient.…”
Section: Discussionmentioning
confidence: 99%